88.4k views
4 votes
In simplified exponential notation, the expression x ³ · x -4 · x = _____

1/x

0

1

User Fose
by
4.9k points

2 Answers

3 votes

Answer: Last option

Explanation:

You need to remember the Negative exponent rule:


a^(-1)=(1)/(a)

You also need to remember the Product ot poers property and the Quotient of powers property, which are:


a^m*a^n=a^((m+n))\\\\(a^m)/(a^n)=a^((m-n))

And:


a^0=1

Therefore, you can rewrite the expression as following:


(x^3*x)/(x^4)

Applying the properties, you can simplify:


=(x^4)/(x^4)\\\\=x^0\\=1

User Msvcyc
by
5.3k points
4 votes

ANSWER

1

EXPLANATION

We want to simplify:


{x}^(3) \bullet \: {x}^( - 4) \bullet \: x

Recall that:


{a}^(m) * {a}^(n) = {a}^(m + n)

We use this property of exponents to get:


{x}^(3) \bullet \: {x}^( - 4) \bullet \: x = {x}^(3 + - 4 + 1)


{x}^(3) \bullet \: {x}^( - 4) \bullet \: x = {x}^(0)

Any non-zero number to the exponent of zero is 1.


{x}^(3) \bullet \: {x}^( - 4) \bullet \: x = 1

User Aushin
by
4.9k points